Loss of RBPj in postnatal excitatory neurons does not cause neurodegeneration or memory impairments in aged mice. - Chihiro Sato (Public Library of Science (PLoS), 2012)
Previous studies suggest that loss of γ-secretase activity in postnatal mouse brains causes age-dependent memory impairment and neurodegeneration. Due to the diverse array of γ-secretase substrates, it remains to be demonstrated whether loss of cleavage of any specific substrate(s) is responsible for these defects. The bulk of the phenotypes observed in mammals deficient for γ-secretase or exposed to γ-secretase inhibitors are caused by the loss of Notch receptor proteolysis. Accordingly, inhibition of Notch signaling is the main cause for untoward effects for γ-secretase inhibitors as therapeutics for Alzheimer's disease. Therefore, we wished to determine if loss of canonical Notch signaling is responsible for the age-dependent neurodegeneration observed upon γ-secrectase deficiency in the mouse brain. We generated postnatal forebrain-specific RBPj conditional knockout (cKO) mice using the CamKII-Cre driver and examined behavior and brain pathology in 12-18 month old animals. Since all four mammalian Notch receptor homologues signal via this DNA binding protein, these mice lack canonical Notch signaling. We found that loss of RBPj in mature excitatory neurons was well tolerated, with no evidence for neurodegeneration or of learning and memory impairment in mice aged up to 18 months. The only phenotypic deficit we observed in the RBPj-deficient mice was a subtle abnormality in olfactory preferences, particularly in females. We conclude that the loss of canonical Notch signaling through the four receptors is not responsible for age-dependent neurodegeneration or learning and memory deficits seen in γ-secretase deficient mice.